Proceedings of the Sixth Workshop on Computational Linguistics and Clinical Psychology 2019
DOI: 10.18653/v1/w19-3010
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Characteristics of Schizophrenic Speech

Abstract: Natural language processing tools are used to automatically detect disturbances in transcribed speech of schizophrenia inpatients who speak Hebrew. We measure topic mutation over time and show that controls maintain more cohesive speech than inpatients. We also examine differences in how inpatients and controls use adjectives and adverbs to describe content words and show that the ones used by controls are more common than the those of inpatients. We provide experimental results and show their potential for au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
1
18
1
Order By: Relevance
“…Iter et al ( 13 ) recently improved LSA-based models ( 11 , 12 ) by preprocessing their data set, filtering stop words and fillers and using modern word and sentence embeddings that were shown to outperform LSA ( 29 , 30 ). Word embeddings were also used by Rezaii, Walker, and Wolff ( 31 ) who were able to predict psychosis onset in high-risk individuals based on word embeddings and participants’ choice of words, and Bar et al ( 32 ) who found that NAP patients adhered less to a topic throughout a conversation than controls. Word embeddings such as Global Vectors for Word Representation [GloVe; ( 33 )] create a vector space based on a large number of texts.…”
Section: Introductionmentioning
confidence: 99%
“…Iter et al ( 13 ) recently improved LSA-based models ( 11 , 12 ) by preprocessing their data set, filtering stop words and fillers and using modern word and sentence embeddings that were shown to outperform LSA ( 29 , 30 ). Word embeddings were also used by Rezaii, Walker, and Wolff ( 31 ) who were able to predict psychosis onset in high-risk individuals based on word embeddings and participants’ choice of words, and Bar et al ( 32 ) who found that NAP patients adhered less to a topic throughout a conversation than controls. Word embeddings such as Global Vectors for Word Representation [GloVe; ( 33 )] create a vector space based on a large number of texts.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 52 articles that were examined only eight discussed the implications of how the language we express is influenced by our identity and demographic features. The articles that did discuss the influence of social factors predominantly focused on the influence of personality and educational level in on the outputs of the NLP models [9,10,[39][40][41][42][43][44][45]. Of the eight studies, two studies provided a table of the demographic features of the initial dataset, however no studies stratified the outputs of their NLP models by by demographic features.…”
Section: Expression Of Datamentioning
confidence: 99%
“…Lexical approaches have been the mainstay of NLP models which use tokenization of text corpora and then attempt to infer the sentimental meaning of the corpus [5,46]. In recent years, more novel AI approaches have evolved which utilize deep learning and neural nets to understand PLOS ONE language and infer sentiment/meaning [32,[41][42][43][44][45]. Part of this approach includes the use of 'word embeddings', which will be a key focus of this study.…”
Section: Analysis Of Datamentioning
confidence: 99%
“…Though the use of NLP for mental health research and practice is growing, its application to the schizophrenia spectrum has only begun to realize its potential. The common approach used by researchers implementing NLP to study schizophrenia is to develop classifiers predicting the presence or future development of the disease, primarily by identifying signs of associative thinking (Bar, Zilberstein, Ziv et al ., 2019; Bedi, Carrillo, Cecchi et al ., 2015; Iter, Yoon & Jurafsky, 2018; Rezaii, Walker & Wolff, 2019). However, to the best of our knowledge, there is no systematic characterization of morphological differences in the language used by patients diagnosed with schizophrenia relative to the general population.…”
Section: Introductionmentioning
confidence: 99%